Transformasi Digital Layanan Kenotariatan: Tantangan Literasi dan Integrasi Sosial pada Masyarakat Pedesaan - Rafiq Adi Wardana (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
Digitalization of legal services is part of the transformation of public services that promotes efficiency, transparency, and accessibility, including in the notary sector. However, its utilization in rural areas faces challenges such as low digital literacy and limited infrastructure. This study aims to analyze (1) the level of digital literacy among rural communities in utilizing digital-based notary services, and (2) the effectiveness of these services in improving legal access in villages. The research method used is normative juridical, supported by qualitative data obtained through literature studies, interviews with notaries, and focus group discussions with village officials. The results indicate that the level of digital literacy among rural communities is still relatively low, but there is potential for improvement through ongoing mentoring and integration with village government programs. Meanwhile, digital-based notary services are considered quite effective in accelerating legal administration processes, although they require a more stringent legal framework and adequate technological infrastructure support. This study concludes that the development of digital notary services in rural areas can be a strategic innovation to improve legal access, provided there is multi-stakeholder collaboration and strengthened regulations.